The use of an ex vivo contrast study at the time of surgery to confirm the site of a perforated jejunal diverticulum. (3rd January 2013) - Zamani, Amin; Peters, Christopher John; Chadwick, Stephen J
Abstract : A 63-year-old patient was diagnosed with acute jejunal diverticulitis and possible perforation. The patient was taken to the operating room for an exploratory laparotomy where a suspected segment of small bowel was resected. However, the surgical team was unsure whether the resected segment was the definite location of the perforation. A novel technique; using intraoperative contrast enhanced ex vivo x-ray photographs aided the surgical team in finding the exact location of the perforation and thus allowing the operating team to confidently and safely proceed with closure of the abdomen.